1961
DOI: 10.1111/j.1476-5381.1961.tb01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Increased Susceptibility to Fibrillation of the Hypothermic Mammalian Heart in Situ

Abstract: The susceptibility of auricles and ventricles to fibrillation during hypothermia of isolated hearts, and of hearts in situ in anaesthetized cats, was estimated by measuring the threshold for the production of fibrillation by electrical stimulation. Hypothermia reduced the threshold of in situ hearts, but increased the threshold of isolated perfused hearts and of heart-lung preparations. The increased sensitivity of in situ hearts to fibrillation could be induced by cooling the head only, and was abolished by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1964
1964
1981
1981

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Arrhythmias were at no time observed in any dog during UK14275 administration. Adrenergic mechanisms are believed however to play an important role in arrhythmogenesis under conditions such as ischaemia (Ceremuzynski, Staszewska-Barczak & Herbacynska-Cedro, 1969;Jewitt et al, 1969), hypothermia (Szekeres, Mehes & Papp, 1961) excessive neurogenic stimulation (Han,Garcia de Jalon & Moe, 1964) or digitalis toxicity and UK14275 might therefore produce similar responses under such conditions. No electrophysiological effect of UK14275 not attributable to an adrenergic mechanism was noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias were at no time observed in any dog during UK14275 administration. Adrenergic mechanisms are believed however to play an important role in arrhythmogenesis under conditions such as ischaemia (Ceremuzynski, Staszewska-Barczak & Herbacynska-Cedro, 1969;Jewitt et al, 1969), hypothermia (Szekeres, Mehes & Papp, 1961) excessive neurogenic stimulation (Han,Garcia de Jalon & Moe, 1964) or digitalis toxicity and UK14275 might therefore produce similar responses under such conditions. No electrophysiological effect of UK14275 not attributable to an adrenergic mechanism was noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent evidence has indicated that a-receptor blockade does contri(bute to protection against arrhythmias induced by oualbain (Barrett & Cullum, 1968;Raper & Wale, 1968;Dohadwalla, Freedberg & Vaughan Williams, 1969) or by acetylcholine (Hashimoto, Chiba, Tanaka, Hirata & Suzuki, 1968). Surgical removal of cardiac sympathetic nerves raises the fibrillation threshold in the cat (Szekeres, Mehes & Papp, 1961;Papp & Szekeres, 1967), and it is possilble that the anti-arrhythmic action of bretylium could be due to depression of activity in sympathetic nerves. Leveque (1965) observed that bretylium did not exhilbit maximum anti-arrhythmic effectiveness until after 4 hr.…”
Section: Discussionmentioning
confidence: 99%